Structural analysis of ZnO nanowires synthesized by using a low-temperature hydro-thermal method - Lee, S; Lee, J; Ko, W; Kang, T; Hong, J; Cha, S (2012)
The structural properties of vertically aligned ZnO nanowires (NWs) prepared using hydrothermal synthesis at various temperatures and different precursor concentrations are systematically described. The ZnO NWs were synthesized on ZnO seed layers via an aqueous solution method with zinc nitrate (Zn(NO 3) 2·6H 2O) hexahydrate and hexamethylenetetramine (HMT). The growth speed and the shape of the ZnO NWs were determined for various mole concentrations. A structural analysis of the ZnO NWs was performed using X-ray diffraction, scanning electron microscopy and tunneling electron microscopy. Finally, the correlation of structural results with growth conditions, such as the mole concentration and the growth temperature of chemical precursors, based on Gibbs free energy. © 2012 The Korean Physical Society.